Effect of Rare Earth Ce on the Microstructure and Mechanical Properties of 34CrNiMo6 Steel for Wind Turbine Main Shaft - Yanming Ge; Kehong Wang (Advances in Materials Science and Engineering)
The effect of rare earth Ce on mechanical properties is studied by investigating the precipitates evolution during heat treatment of 34CrNiMo6 steel. Five different rare earth Ce contents are carried out with the same holding time 3 hours. Then, the mechanical properties of 34CrNiMo6 steel are obtained under steady state conditions and impact conditions, respectively. The strength decreases while the elongation after breakage increases with the rare earth Ce content increasing. The impact absorbing energy at 20°C and −40°C increases with the rare earth Ce content increasing. Based on the experimental results, the recommended rare earth Ce content is 0.05 wt.%. The differences in mechanical properties among the different rare earth Ce contents may be the nucleation rate and growth of precipitates under different conditions. The spherification degree of cementite is more complete with rare earth Ce content, resulting in the decrease of mechanical properties and improvement of ductility.